An Exploratory study on the perceptions of former divertees on the factors that contributed to their non-compliance with diversion orders in the Central Karoo (Western Cape, South Africa) - Weëls, Sanna (Department of Social Development, 2021)
Non-compliance with court diversion orders by child divertees remain a challenge within the child justice system in South Africa. The overall aim of the study was to explore the perceptions of former divertees regarding the factors that contributed to their non-compliance with diversion orders. Qualitative research approach and a purposive sampling technique were adopted. Non-probability sampling was utilised to draw purposive sampling. Semi-structured one-to-one interviews were used as the method of data collection. There were 15 male participants between the ages of 15 and 21 years who represented the dominant gender type diverted in the rural courts of the Central Karoo. The study showed children diverted had a basic understanding of what diversion entails and the consequences for failing to comply with the diversion court orders. However, economic challenges in households played a significant role in non-compliance with diversion orders as some divertees chose temporary job opportunities over diversion programme attendance. Furthermore, the study revealed that diversion programmes do not offer food, and this affected their concentration level and hindered full participation to benefit from diversion opportunities. Another factor that contributes to non-compliance with diversion orders is a non-supportive child justice system. Courts showed inconsistency in the management of diversion, as some courts do act on noncompliance with diversion orders whilst others do not. Lack of proper support and monitoring by both probation officers and parents put divertees at risk of non-compliance with diversion orders. However, some divertees defied their diversion orders by not attending programmes. Association with older friends and smoking dagga for a greater part of their day put further risk on successful completion of diversion programmes. To encourage full diversion programme attendance, it is recommended that diversion service providers provide food for the divertees before the start of each session. Effective monitoring and follow-up of diversion programmes by probation officers are important to ensure compliance. Furthermore, to achieve long-term behavioural change and minimise the chances that divertees abandon diversion, it is recommended that diversion sessions include different facilitation methods such as physical activities to keep the divertees interest in attending.